Girls, let's talk about sex and Islam : a study on young Singaporean Muslim women and how they make sense of sexual agency and religion in contemporary Singapore - Nadya Nasser (2013)
In today’s contemporary Singapore, young Singaporean Muslim women face opposing pressures from the modern and secular ethos that permeates their lives on one hand, and the standards of ‘piety’ and ‘modesty’ placed on them by religion on the other. This study aims to explore: How then do they negotiate their religion and sexual behaviour, and conceptualize their agency in these issues? The theories of “plausibility structures” and privatisation of religion are crucial in trying to show how religiosity depends on one’s social circle and her intensity of engagement in religious rituals. Also, this study will demonstrate how Singapore’s political frameworks as an external influence of change affects religious practice and in turn, what it means to be a young Singaporean Malay Muslim woman.